A novel colorimetric and ratiometric fluorescent CN− sensor based on rhodamine B hydrazone derivatives in aqueous media and its application in sprouting potatoes. (26th September 2018) - Long, Chen; Hu, Jing-Han; Ni, Peng-Wei; Yin, Zhi-yuan; Fu, Qing-Qing
Abstract : A novel cyanide specifically selective and highly sensitive chemosensorZ based on rhodamine B hydrazone derivatives had been designed and synthesized. Abstract : A novel highly selective chemosensorZ based on rhodamine B hydrazone derivatives was designed and synthesized, and it showed both colorimetric and "turn-on" fluorescence responses for CN − in an aqueous solution. The results showed that after adding CN − ions in aqueous solution, the chemosensorZ showed significant color change from colorless to pale-yellow, which was visible to the naked eye, and it rapidly produced strong green fluorescence. The probe could distinguish CN − by deprotonation and intramolecular charge transfer (ICT) mechanisms, as evidenced by 1 H-NMR titration and DFT calculations. In addition, the detection limit of the fluorescence response of the sensor for CN − was 5.81 × 10 −8 M, which was measured by titration. The chemosensorZ has been successfully used to detect CN − in sprouting potatoes.Z -containing test strips have also been prepared, and they can be used as a colorimetric tool for CN − detection in potential applications.